Pengaruh Model Supervisi Klinis Interaktif Proctor oleh Perawat terhadap Akurasi Implementasi Komunikasi Efektif Melalui SBAR dan TBAK - Sarti Oktarina Purba; Emiliana Tarigan; Wilhelmus Harry Susilo; Loritta Yemina (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2026)
Effective communication through the Situation, Background, Assessment, Recommendation (SBAR) and Write, Read, Confirm (TBAK) methods is an important strategy in improving patient safety; however, the accuracy of its implementation still needs to be strengthened through effective clinical supervision. One way to ensure the quality of service is by implementing the interactive proctor clinical supervision model. The purpose of this study is to analyze, predict, and explore the impact of the implementation of the Team Leader Proctor Clinical Supervision Model on the implementation of patient safety, especially in terms of effective communication through SBAR and TBAK by nurses at Hospital X Jakarta. The research method is quasi-experimental, involving pre-posttest testing with a control group. The number of respondents was 90 people, consisting of 68 people in the intervention group and 22 people in the control group. Results of the study: After being given the Interactive Proctor clinical supervision model intervention, there was an increase of 73.5% according to standards, and 26.5% did not meet standards. Therefore, there is a significant influence of the Interactive Proctor clinical supervision model intervention on patient safety, especially in terms of the ability to communicate effectively through SBAR and TBAK, with a p-value of 0.000 (<0.05). The conclusion shows that the Proctor clinical supervision model increases the implementation of effective communication using SBAR and TBAK.